2017
DOI: 10.1016/j.enbuild.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Application of the cost-optimal methodology to urban renewal projects at the territorial scale based on statistical data—A case study in Spain

Abstract: As tomorrow's cities are already largely built, many strategies stress the importance of urban renewal processes to address current energy issues. This paper focuses on the Spanish residential building stock built until 2001, which has a low level of energy performance.Considering the current economic crisis, the future lies in renovating the built environment, which holds a significant energy-saving potential. This potential is here quantified by applying the cost-optimal methodology, initially proposed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…These regulations have restricted both heating and cooling energy demands and have established maximum thermal transmittances for the elements that make up the thermal envelope of a building, depending on the climate zone in which the building is located. The most effective method for the energy refurbishment of the residential building stock is to increase the thermal insulation of the opaque elements of the thermal envelope; this increased insulation achieved average energy savings of 45% in Italy [12] and 40% in Spain [13]. In addition, Varela Luján et al [14] found that, in Spain, renovating façades using external thermal insulation composites reduced energy losses by 57% and energy gains by 39% compared to those with the façade in its original state.…”
Section: Introductionmentioning
confidence: 99%
“…These regulations have restricted both heating and cooling energy demands and have established maximum thermal transmittances for the elements that make up the thermal envelope of a building, depending on the climate zone in which the building is located. The most effective method for the energy refurbishment of the residential building stock is to increase the thermal insulation of the opaque elements of the thermal envelope; this increased insulation achieved average energy savings of 45% in Italy [12] and 40% in Spain [13]. In addition, Varela Luján et al [14] found that, in Spain, renovating façades using external thermal insulation composites reduced energy losses by 57% and energy gains by 39% compared to those with the façade in its original state.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most case studies (23 of 30) used financial models to evaluate the retrofit's economic performance, although in the other case studies, authors simply calculated the energy savings number, as was suggested in the US Department of Energy guides described in the previous section. The authors note three popular approaches for financial evaluation: life cycle cost (Amiri et al, 2018;Becchio et al, 2016;Jafari 2017;Qian Wang et al, 2014), payback period (Aguacil et al,2017;Ashrafian et al, 2016;Tahsildoost et al, 2015), and net present value (Becchio et al, 2016;Hosseinian et al, 2017;Senel Solmaz et al, 2018;Qinpeng Wang et al, 2017). All of these approaches focus on the economic benefits of the life-long service of the building, say, the energy savings from daily operation subtracting the initial cost of retrofit projects.…”
Section: Case Study Reviewmentioning
confidence: 99%
“…Lastly, renewable energy resources should be integrated with the active systems to reduce the fuel consumption and CO2 emission associated with it. Aguacil et al [9] indicated that passive strategies could provide 40% of energy saving, while it is possible to reach 80% saving by combining passive strategies with active ones.…”
Section: Introductionmentioning
confidence: 99%